PENGEMBANGAN LEMBAR KERJA SISWA DENGAN PENDEKATAN SCIENTIFIC APPROACH BERMUATAN NILAI KEWIRAUSAHAN UNTUK SISWA KELAS IV - Ika Silfiana Arifatul Khoiriyah; Alifia Cahya Wicaksani (Universitas Negeri Medan, 2019)
Abstract : Development of Student Worksheets with a Scientific Approach with Entrepreneurship Values for Class IV Students. The research method used in the development of worksheets with a scientific approach with an entrepreneurial value on the theme of this work is the research and development method with the 4D model (Define, Design, Develop and Disemination). The results of this study are: (1) the development of student worksheets with a scientific approach with an entrepreneurial value on the theme of various jobs. The feasibility assessment by media experts got an average score of 115 with an average score of 3.96 which was included in the very feasible category. As well as the average number of scores of 105.2 obtained from the assessment of students with a mean score of 3.5 which is included in the category of very feasible as teaching material and is in the percentage of a very decent category of 100%.Keywords: Student worksheet, Scientific Approach, Value of EntrepreneurshipAbstrak : Pengembangan Lembar Kerja Siswa Dengan Pendekatan Scientific Approach Bermuatan Nilai Kewirausahan Untuk Siswa Kelas IV. Metode penelitian yang digunakan dalam pengembangan lembar kerja dengan pendekatan ilmiah dengan nilai kewirausahaan pada tema karya ini adalah metode penelitian dan pengembangan dengan model 4D (Define, Design, Develop and Disemination). Hasil dari penelitian ini adalah: (1) pengembangan lembar kerja siswa dengan pendekatan ilmiah dengan nilai kewirausahaan pada tema berbagai pekerjaan. Penilaian kelayakan oleh para pakar media mendapat skor rata-rata 115 dengan skor rata-rata 3,96 yang termasuk dalam kategori sangat layak. Serta jumlah rata-rata skor 105,2 diperoleh dari penilaian siswa dengan nilai rata-rata 3,5 yang termasuk dalam kategori sangat layak sebagai bahan ajar dan dalam persentase kategori sangat layak 100%.Kata kunci: Lembar kerja siswa, Scientific Approach, Nilai Kewirausahaan